2015
DOI: 10.1056/nejmoa1512614
|View full text |Cite
|
Sign up to set email alerts
|

Sofosbuvir and Velpatasvir for HCV in Patients with Decompensated Cirrhosis

Abstract: Treatment with sofosbuvir-velpatasvir with or without ribavirin for 12 weeks and with sofosbuvir-velpatasvir for 24 weeks resulted in high rates of sustained virologic response in patients with HCV infection and decompensated cirrhosis. (Funded by Gilead Sciences; ASTRAL-4 ClinicalTrials.gov number, NCT02201901.).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

57
729
2
19

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 722 publications
(807 citation statements)
references
References 10 publications
57
729
2
19
Order By: Relevance
“…The inclusion criteria for EAP treatment was patients with significant risk of death or irreversible harm within 12 months, mostly with decompensated cirrhosis. Markers of liver disease severity such as MELD score and platelet count were similar to other studies of HCV treatment in decompensated patients (SOLAR-1, ASTRAL-4) [6,14]. Within the decompensated subgroup, 17% patients were Child Pugh class A at baseline, but had past decompensation events, and therefore remained at significant risk from severe liver disease.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…The inclusion criteria for EAP treatment was patients with significant risk of death or irreversible harm within 12 months, mostly with decompensated cirrhosis. Markers of liver disease severity such as MELD score and platelet count were similar to other studies of HCV treatment in decompensated patients (SOLAR-1, ASTRAL-4) [6,14]. Within the decompensated subgroup, 17% patients were Child Pugh class A at baseline, but had past decompensation events, and therefore remained at significant risk from severe liver disease.…”
Section: Discussionsupporting
confidence: 77%
“…The study was not powered to detect significance between the three treatment groups, but the addition of ribavirin increased SVR, and to a greater extent than the 24 week duration, particularly in genotype 3 infected patients. [14] Not unexpectedly from this population with advanced disease, serious adverse events were common, comprising mainly events related to end-stage liver disease. However, treatment was well tolerated with few premature discontinuations.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Worldwide, large numbers of HCV-infected patients with decompensated cirrhosis have received antiviral therapy and although sustained virological response (SVR) rates are slightly reduced compared to patients with compensated disease, over 80% of treated patients still achieve viral clearance. Early analysis of patients who responded to therapy showed associated improvements in MELD and Child Pugh scores [1] [2][3][4], although some concerns have been expressed that the rate of malignancy may not change or may, paradoxically, increase [5,6]. Previous studies of interferon-based therapies have demonstrated that HCV clearance improves liver fibrosis, even in cirrhosis [7].…”
Section: Introductionmentioning
confidence: 99%
“…Currently, the only Food and Drug Administration‐approved options for children with chronic HCV infection are ribavirin (RBV) and pegylated‐interferon (PEG‐IFN). While sustained viral responses (SVRs) have improved over the last several decades from ∼16% with IFN monotherapy to >50% with the combination of RBV and PEG‐IFN, multiple studies have shown that SVR rates remain frustratingly low compared to adults with access to DAA regimens 6, 13, 100, 101, 102, 103, 104, 105, 106, 107, 108, 109, 110, 111, 112, 113, 114, 115, 116. Consequently, in the absence of approved DAA therapies in the United States, the chance of attaining SVR in HCV‐infected children and adolescents is little more than 50% (Table 4).…”
Section: Managementmentioning
confidence: 99%